Analysis of Cocoa Seedling Growth (Theobroma cacao L.) in Applications Foliar Fertilizer and Frequency of Watering - Charloq, Charloq (UNIVERSITAS LABUHANBATU, 2024)
Growth response of cacao seedlings (Theobroma cacao L) on foliar fertilizer application and the right frequency of water application is done so that the needs of nutrients and water are met for cacao seedlings in the nursery. This study aims to analyze the growth of cocoa seedlings (Theobroma cacao L) on foliar fertilizer application and frequency of water application. This research uses a Factorial Randomized Block Design with 2 treatment factors. Factor I: Foliar fertilizer dosage (ml/l water): 0, 4, 6, and 8 and factor II: Frequency of water application: 1, 3, 5 and 7 days. The parameters observed are plant height, stem diameter, number of leaves, total leaf area, leaf thickness, crown dry weight, root dry weight. The results showed that the application of foliar fertilizer at a dose of 8 ml/l water gave the best growth response with significant effect on all observed variables of cocoa seedling growth. Frequency of water application under field capacity conditions has a significant effect on total leaf area and leaf thickness with 1x/day water application. The interaction of the two treatments has no significant effect on all observed variables. Keywords: cocoa seedlings, foliar fertilizer, watering interval